2019
DOI: 10.1111/cea.13314
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up of patients with negative drug provocation tests to betalactams

Abstract: Drug allergy work-up in betalactam (BL) allergy is probably the most-developed drug-allergy evaluation at present. 1 During the last few years, the debate on whether 1-day or several-day (prolonged) drug provocation test (DPT) should be performed in non-immediate reactions (ie, occurring >1 hour after the last administered dose) in order to increase sensitivity has been ongoing and groups working in drug allergy diagnosis have been deploying pro and con arguments and studies in favour of either option. [2][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…These protocols refer to children reporting a history of mild reactions, and the authors suggest that increasing the duration of DPT may improve its diagnostic performance without increasing the risk of severe reactions during the observation period or at home. From our personal experience, there is no advantage in the predictive value of DPT if performed over a 1‐day period (followed by 48 hours of surveillance at home) or over a more prolonged time . Also, in these cases, it seems essential either to examine patients during the reaction or to be able to properly classify it as immediate or non‐immediate, and mild‐moderately (or potentially) severe by means of anamnesis (interview of the parents, and photographies of the reaction).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These protocols refer to children reporting a history of mild reactions, and the authors suggest that increasing the duration of DPT may improve its diagnostic performance without increasing the risk of severe reactions during the observation period or at home. From our personal experience, there is no advantage in the predictive value of DPT if performed over a 1‐day period (followed by 48 hours of surveillance at home) or over a more prolonged time . Also, in these cases, it seems essential either to examine patients during the reaction or to be able to properly classify it as immediate or non‐immediate, and mild‐moderately (or potentially) severe by means of anamnesis (interview of the parents, and photographies of the reaction).…”
Section: Resultsmentioning
confidence: 99%
“…From our personal experience, there is no advantage in the predictive value of DPT if performed over a 1-day period (followed by 48 hours of surveillance at home) or over a more prolonged time. 20 Also, in these cases, it seems essential either to examine patients during the reaction or to be able to properly clas- could be helpful in pediatric settings, regardless the chronology of the initial reaction.…”
Section: Con Clus Ionmentioning
confidence: 99%
“…Nonimmediate reactions following a negative 1‐day or prolonged DPT are described as mild/moderate. Nevertheless, in the studies that carried out 1‐day DPT, the rate of subjects who have taken again the BL concerned in real‐life conditions ranged from 22% to 39%, whereas in the studies that performed prolonged DPT with BL, such rate ranged from 52% to 71% . Moreover, Ratzon et al found that 100% (n = 18/18) of the patients who had undergone prolonged DPT and needed a BL used it, compared with only 76% (n = 16/21) of patients who had undergone 1‐day DPT.…”
Section: Diagnosismentioning
confidence: 99%
“…If no reaction occurs, DPT is resumed at home with therapeutic doses for several days. [50][51][52][53] Regarding NSAIDs, it was suggested to consider their absorption speed to determine steps for DPT. 54 The optimal total cumulative dose for DPT is also under debate.…”
Section: Drug Provocation Testmentioning
confidence: 99%